Preliminary studies on Odour pollution from Fishmeal factory - Justin Sentian (Universiti Malaysia Sabah, 2002)
Complaints from the public have been reported frequently to the respective authorities concerning odour emission from the fis1uneal factory at Sepangar Bay Kota Kinabalu. PreIiminaty study has been carried out at the fishmeal factory to determine the point sources of odour emission and to assess the pollution control facilities to abate odour pollution. It was found that the major sources of odour pollution were from the cooking and drying processes. From the observation, the pollution control facilities to abate odour pollution, physically capable to minimize the odour pollution. However, the efficiency of the pollution control was not studied in detail.